Предмет: Алгебра,
автор: volodymyr27072007
(1-cos2x)(1+cos2x)-2
Ответы
Автор ответа:
1
Відповідь: - ( cos4x + 3 )/2 .
Пояснення:
( 1 - cos2x )( 1 + cos2x ) - 2 = ( 1 - cos²2x ) - 2 = sin²2x - 2 =
= - ( 1 - sin²2x ) - 1 = - cos²2x - 1 = - ( 1 + cos4x )/2 - 1 =
= - 1/2 - 1/2 cos4x - 1 = - ( cos4x + 3 )/2 .
Похожие вопросы
Предмет: Английский язык,
автор: lrosikovska
Предмет: Математика,
автор: 12groof12
Предмет: Биология,
автор: Chyvak5
Предмет: Английский язык,
автор: islamsajdullaev2007
Предмет: Алгебра,
автор: ondarayusha1